Commitment - Simpson, Mona (Alfred A. Knopf, 2023)
"The story of a family whose single mom, fighting mental illness, slowly becomes unable to raise her family, told from the perspective of each of the three children. As the novel opens, a mother drives her eldest son Walter from their home in Los Angeles to the University of California at Berkeley. It will be her last fully responsible act before breaking down completely and being committed to a mental hospital, leaving her children behind. Holding tight to his ambitions to become an architect, Walter must cope with the sudden loss of his family and all financial support. With the help of a family friend, his younger sister and brother, still at home, barely manage to escape social services and foster care, but they must fend for themselves as they try to finish school and begin searching for their own careers. We hear each of them tell their own story as they witness the slow disappearance of their beloved mother into mental illness while they struggle to achieve the life she envisioned for them and to keep the family intact"--